The development of computational thinking modules for grade VII students to improve problem-solving skills - Utomo, Beni; Rosa, Paulina Heruningsih Prima; Ernawati, Nur; Jazuli, Muhammad Khanafi; Widarti, Fatwa Ika; Amalia, Nanda (Proceedings of International Conference on Research in Education, 2025)
This study aims to develop a computational thinking module for seventh-grade students. The type of research is research and development. The method used is ADDIE. The research was conducted by analyzing students’ needs for computational thinking modules. The needs analysis stage is carried out by collecting data regarding the curriculum used by the school, the curriculum regarding coding and artificial intelligence, and school development in the self-improvement class subject. Based on these needs, the modules were designed and developed according to learning outcomes and school characteristics. The implementation was conducted in SMP Islam Al Azhar 26 Yogyakarta on July 2025.